Spotters in Pediatrics - Verma Anoop, Parag Pulak, Bhatt Ramesh, Sharma Sanjay; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2008)
The syndromic child is most of the time considered a gift of God and hence, further treatment by parents comes to an end. It is on the part of treating physician to counsel such parents and make them aware of the condition and accordingly encourage future course of disease and its inheritance. There are certain conditions which have strong possibility and probability to recur in future generation, on the contrary, there are conditions which almost occurs once (sporadic mutation). The concept of counseling should spread to all parents of such children. Rarely do we find parents who are concerned of their child$1 (Bs disease and its course. The usefulness of a clinical atlas in medicine is known since ages. The present shape of (3z(BSpotters in Pediatrics(3y (Bis the result of years of devotion and hard work. With its classified and authoritative format this atlas supplies the answer to question that may arise during examination or consultation, giving advice on symptoms, diagnosis and therapeutic measures. This book is an excellent collection of clinical photographs of common to rare pediatric diseases along with short text for ready reference. It will definitely prove to be a guiding source of knowledge for the busy practicing pediatrician and will serve as ready reckoner.s
Keywords: Pediatrics; Electronic books